Influence of physical protectors with different filters on the initial development of Peltophorum dubium (Spreng.) Taub seedlings - Klein, Jeferson; Rodrigues, João Domingos [UNESP]; Guimaraes, Vandeir Francisco; Rampim, Leandro; Kestring, Debora; Schwantes, Daniel; Fey, Rubens; Aleixo, Valdemir; Richart, Alfredo; Ferronato, Michelli Carline; Borsoi, Augustinho (Academic Journals, 2014)
The use of physical protectors has been considered as an efficient technique for tillage farming of different species, mainly native ones. Based on the importance of the species, Peltophorum dubium for revegetation of degraded areas, this study evaluated the emergence, survival and initial development of P. dubium seedlings under the influence of physical protectors with different filters. Thus, the following treatments were adopted: absence of physical protector (APP), transparent physical protector (TPP), transparent physical protector + blue cellophane (BPP) and transparent physical protector + red cellophane (RPP). The evaluated characteristics were: emergence velocity index (EVI), seedling survival and emergence percentage, plant height, leaf area and root collar diameter. All of these physical protectors increased the mean values of EVI and survival. In conclusion, the emergence speed and initial development of P. dubium (Spreng.) seedlings grown in the interior of physical protectors, independent on the filters, presented positive results. The reduction on the light intensity interferes positively in the initial growth of these plants.
Keywords: Native species; Reforestation; Seedlings; Reflorestamento; Taxa fotossintética